Adaptive path-following control for bio-inspired steerable needles - Secoli,R; Rodriguez,y Baena F (IEEE, 2016)
Needle steering systems have shown potential ad-vantages in minimally invasive surgery in soft-tissue due to theirability to reach deep-seated targets while avoiding obstacles. Ingeneral, the control strategies employed to drive the insertionuse simplified kinematic models, providing limited control ofthe trajectory between an entry site and a deep seated targetin cases of unmodelled tissue-needle dynamics. In this work,we present the first Adaptive Path-Following (APF) controllerfor a bio-inspired multi-part needle, able to steer along three-dimensional (3D) paths within a compliant medium by meansof the cyclical motion of interlocked segments and without theneed for duty-cycle spinning along the insertion axis.The control strategy is outlined in two parts: a high-level con-troller, which provides driving commands to follow a predefined3D path smoothly; and a low-level controller, able to counteractunmodelled tissue-needle nonlinearities and kinematic modeluncertainties. A simulation that mimics the needle’s mechanicalbehavior during insertion is achieved by using an ExperimentalFitting Model (EFM), obtained from previous experimentaltrials. The Simulation results demonstrate the robustness andadaptability of the proposed control strategy.